Stock Prices and Accounting Information: A Review of the State of Play - Scott Pirie; Malcolm Smith (Journal of Accounting, Business and Management (JABM), 2008)
One of the aims of financial statements is to provide relevant information to support investment decisions. Consequently, relationships between share prices and accounting variables have been widely researched. Early studies focus mainly on earnings, but attention has turned in recent years to valuation models that include the book value of the equity. Many of these studies cite the residual income model as their theoretical base and, with the growing emphasis on shareholder value, residual income measures have become more widely used by the business community to track financial performance. Given these trends, this paper reviews the theoretical background of the residual income model and discusses the results of empirical studies based upon it. It finds that the two main accounting variables can usually explain a substantial part of the variance in share prices, and can also be useful in predicting future returns. However, a number of practical issues remain unresolved. These findings should be of interest to other researchers, and should also be helpful to managers and investors who currently use, or are planning to use, residual income or similar accounting-based measures to monitor and forecast business performance.